Association between community-level social trust and the risk of dementia: A retrospective cohort study in the Republic of Korea - Jaeyi Hong; Jaeyi Hong; Sun Jae Park; Jong-Koo Lee; Hye Jin Jeong; Hye Jin Jeong; Juhwan Oh; Seulggie Choi; Seulggie Choi; Seogsong Jeong; Kyae Hyung Kim; Kyae Hyung Kim; et al. (Frontiers Media S.A., 2022)
IntroductionIt is known that biological risk factors and lifestyle behaviors are important determinants of dementia. However, there has been yet to be sufficient evidence to prove that community-level social capital is one of the determinants of dementia. This retrospective cohort study is a large, long-term, population-based study that investigated the association between community-level social trust and the risk of dementia in the Republic of Korea.MethodsData came from the Korean National Health Insurance Service database. The community-level social trust values were determined by the Korean Community Health Survey. The study population consisted of 1,974,944 participants over 50 years of age and was followed up from 1 January 2012 to 31 December 2019 with a latent period of 5 years from 1 January 2012 to 31 December 2016. Cox proportional hazards regression was utilized to obtain the adjusted hazard ratios (aHRs) and 95% confidence intervals (CIs) for the risk of dementia according to social trust quintiles.ResultsParticipants within the highest quintile of community-level social trust had a lower risk for overall dementia (aHR, 0.90; 95% CI, 0.86-0.94) and Alzheimer's disease (aHR, 0.90; 95% CI, 0.85-0.94) compared to those within the lowest quintile of community-level social trust. The alleviating trend association of high community-level social trust on dementia risk was maintained regardless of whether the participants had health examinations.ConclusionsOur findings suggest that higher community-level social trust is associated with a reduced risk of dementia. Community-level social trust is a crucial indicator of dementia and improving community-level social trust may lead to a lower risk of dementia.